THE EFFECT OF AIRPORT PERSONNEL’S KNOWLEDGE OF EMERGENCY FACILITIES ON THE SAFETY OF TERMINAL BUILDING OCCUPANTS AT UPBU CLASS II SULTAN BABULLAH TERNATE - Fatimah, Siti; Arsiyatama Baharsyah, Aditya; Maharani Sukma, Meita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The safety of terminal building occupants is a critical aspect of airport operations, especially in disaster-prone areas such as Ternate. This study aims to determine the influence of airport personnel’s knowledge of emergency facilities on the safety of terminal occupants at UPBU Class II Sultan Babullah Ternate. Using a quantitative approach and descriptive-associative method, data were collected through questionnaires distributed to 46 operational personnel. The Spearman Rank correlation test showed a significant relationship (r = 0.344; sig. = 0.000), while the simple linear regression analysis indicated that personnel knowledge accounted for 11.2% of the variance in occupant safety. Findings reveal limited technical understanding among personnel and weak coordination during emergency situations. Therefore, enhancing practical training and strengthening internal coordination systems are essential to support risk mitigation efforts within the airport terminal environment.